Development of Learning Media for the Katapel Quiz Application on the Concept of Energy in Living Systems - Sridiyanti S. Dunggio; Tirtawaty Abdjul; Citron S. Payu; Masrid Pikoli; Ritin Uloli; Abdul Haris Odja (Postgraduate, University of Mataram, 2024)
This research aims to produce a product and describe the validity, practicality, and effectiveness of the Katapel quiz application learning media on energy in living systems. The research method used is Research and Development (R&D) research and uses the 4D development model. The research target was class VII of SMP Negeri 1 Asparaga, involving 22 students. The results of Katapel quiz application consist of validity obtained 3.73 in the